Psychiatry - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Explores psychiatry, the medical specialty devoted to the study, diagnosis, treatment, and prevention of mental disorders.
Executive producer, Adem Kalac
MaryLynn Schiavi
DVD format
Keywords: Psychiatry; Mental disorders; Medicine -- Psychiatry